Effect of packaging oxygen transmission rate on the shelf life of ready‐to‐heat foods susceptible to postcontamination during refrigerated and illuminated storage. Issue 3 (28th December 2019) - Baele, Maarten; Vermeulen, An; Leloup, Frédéric; Adons, Dimitri; Peeters, Roos; Devlieghere, Frank; De Meulenaer, Bruno; Ragaert, Peter
Abstract : Since more and more pressure is exerted to reduce the use of plastic packaging materials, optimizing the use of food packaging is opportune. The aim of this study was to evaluate the combined effect of packaging materials, spanning a range of oxygen transmission rates (OTR), and retail illumination, on the microbial shelf life and safety of refrigerated ready‐to‐heat foods. Cooked potato slices were packaged in OPA/PP bags with a high OTR (28.85 ccO2 /m 2 /d) and OPA‐EVOH/PP bags with a low OTR (6.57 ccO2 /m 2 /d). Cooked composite meals were packaged in tray and foil combinations, also spanning a range of OTR: PP trays (2.09 ccO2 /tray/d) with OPA/PP foils (28.85 ccO2 /m 2 /d), PP trays with OPA‐EVOH/PP (6.57 ccO2 /m 2 /d) foils, and PET trays (0.07 ccO2 /tray/d) with PET top foil (32.86 ccO2 /m 2 /d) . The packages were stored in a dark environment, or under fluorescent or LED light. Due to the rapid growth of lactic acid bacteria, the microbial shelf life of both food products was largely unaffected by the type of barrier. Illumination at 1000 lux for 12 hours per day led to temperature differences significantly affecting microbial growth. Based on the results, it could be concluded that re‐evaluating packaging material choices for these foods may prove valuable, since the use of high‐barrier multilayer packaging materials may be considered as a case of overpackaging. Abstract : Cooked refrigerated ready‐to‐heat foods (potato slices and composite meals) were packaged in different packaging materials suggested by food producers, covering a range of O2 transmission rates, with specific attention toward monolayer or less complex materials. The packages were stored either in a dark environment, or under LED or fluorescent illumination. Effects of these packaging materials and illumination conditions on the foods' shelf life were evaluated.